Internship Report: Laying the foundation of the Maize Nutrient Manager (MNM) mobile phone-based app in the Southern Highlands of Tanzania - Kilakila, Mukoma Kitundu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Maize remains one of the most important cereal crops grown in small-holder farming systems in sub-Saharan Africa (SSA)(Cairns et al., 2013). Its cultivation is generally characterized by limited input use and low yields. The low yields are often associated with low soil fertility, pest, and diseases, weeds, low and inappropriate use of inputs such as fertilizers (Sanchez, 2002). This internship aimed to develop a nutrient management advice protocol that was used to inform the development of Maize nutrient Manager (M-N-M) advisory mobile phone app for maize farmers and extension workers in the Southern Highlands of Tanzania. The MNM app advises farmers what type of fertilizer to use, when, and how best to apply it depending on the conditions of the field to improve maize yield